Disabled Persons’ Associations in France - Catherine Barral (Scandinavian Journal of Disability Research, 2007)
In the years following the First World War, the first associations of disabled civilians were formed, to demand the same rights and measures for professional integration as those granted to victims of war and of accidents in the workplace, and to create institutions for rehabilitation. After the Second World War, associations of parents of disabled children began to create specialized institutions for children who were impaired or failing at school. The field of disability was built on the model of rehabilitation in a type of mixed economy, with associations managing institutions and the State financing and regulating them. From the 1980s, the gradual emergence of users’ associations claiming equal rights and the right to autonomy on the one hand, and the “Europeanization” of associative actors on the other, led to a reorientation of public policies.